Aberrant adaptive immune response underlies genetic susceptibility to tuberculosis - Tsareva, Anastasiia; Shelyakin, Pavel V.; Shagina, Irina A.; Myshkin, Mikhail Yu.; Merzlyak, Ekaterina M.; Kriukova, Valeriia V.; Apt, Alexander S.; Linge, Irina A.; Chudakov, Dmitriy M.; Britanova, Olga V. (Frontiers in Immunology, 2024)
Mycobacterium tuberculosis (Mtb) remains a major threat worldwide, although only a fraction of infected individuals develops tuberculosis (TB). TB susceptibility is shaped by multiple genetic factors, and we performed comparative immunological analysis of two mouse strains to uncover relevant mechanisms underlying susceptibility and resistance. C57BL/6 mice are relatively TBresistant, whereas I/St mice are prone to develop severe TB, partly due to the MHC-II allelic variant that shapes suboptimal CD4 + T cell receptor repertoire. We investigated the repertoires of lunginfiltrating helper T cells and B cells at the peak of anti-Mtb immune responses in both strains. We found that lung CD4 + T cell repertoires of infected C57BL/6 but not I/St mice contained convergent TCR clusters with functionally confirmed Mtb specificity. Transcriptomic analysis revealed a more prominent Th1 signature in C57BL/6, and expression of pro-inflammatory IL-16 in I/St lunginfiltrating helper T cells. The two strains also showed distinct Th2 signatures. Furthermore, the humoral response of I/St mice was delayed, less focused, and dominated by IgG/IgM isotypes, whereas C57BL/6 mice generated more Mtb antigen-focused IgA response. We conclude that the inability of I/St mice to produce a timely and efficient anti-Mtb adaptive immune responses arises